Respostas
respondido por:
1
f(x) = 3x² - 5x + 6
f(-2) = 3(-2)² - 5(2) + 6 = 9 - 10 + 6 = 15 -10 = 5
f(4) = 3(4²) - 5(4) + 6 = 48 - 20 + 6 = 54 - 20 = 34
*-*-*-*-*-*-*-*-*-*-*-*
10/10/2016
Sepauto
*-*-*-*-*-*-*-*-*-*-*-*
f(-2) = 3(-2)² - 5(2) + 6 = 9 - 10 + 6 = 15 -10 = 5
f(4) = 3(4²) - 5(4) + 6 = 48 - 20 + 6 = 54 - 20 = 34
*-*-*-*-*-*-*-*-*-*-*-*
10/10/2016
Sepauto
*-*-*-*-*-*-*-*-*-*-*-*
respondido por:
0
f(x) = 3x² - 5x + 6
-----
2
f(-2) = 3.(-2)² - 5.(-2) + 6
----------
2
f(-2) = 3.4 + 10 + 6
----
2
f(-2) = 3.2 + 16
f(-2) = 6 + 16
f(-2) = 22
**********************************
f(4) = 3.4² - 5.4 + 6
-------
2
f(4) = 3.16 - 20 + 6
------
2
f(4) = 3.8 - 14
f(4) = 24 - 14
f(4) = 10
-----
2
f(-2) = 3.(-2)² - 5.(-2) + 6
----------
2
f(-2) = 3.4 + 10 + 6
----
2
f(-2) = 3.2 + 16
f(-2) = 6 + 16
f(-2) = 22
**********************************
f(4) = 3.4² - 5.4 + 6
-------
2
f(4) = 3.16 - 20 + 6
------
2
f(4) = 3.8 - 14
f(4) = 24 - 14
f(4) = 10
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás